2008
DOI: 10.1124/jpet.108.143438
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Tolerance in the Mouse Ileum and Colon

Abstract: Repeated administration of morphine is associated with tolerance to its antinociceptive properties. However, constipation remains the major side effect of chronic exposure to morphine. In contrast, previous studies suggest that tolerance to opioids develops in the ileum of several species. In this study, we provide evidence that constipation may arise due to a lack of tolerance development to morphine in the colon. Mice received implants with either placebo or 75 mg of morphine pellets, and they were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 33 publications
5
83
0
Order By: Relevance
“…Similar to the results in previous studies (Koslo et al, 1986;Heyman et al, 1988;Pol et al, 1999;Ross et al, 2008), we showed that morphine can inhibit gastrointestinal transit mainly through peripheral, and in part through supraspinal as well as spinal, naloxonazine-insensitive sites of m-opioid receptors, whereas morphine inhibits colonic transit through peripheral naloxonazine-sensitive and -insensitive sites of m-opioid receptors. In the present study, we showed that oxycodone and fentanyl inhibit gastrointestinal transit mainly through peripheral m-opioid receptors.…”
Section: Differential Effects Of M-agonists On Intestinal Transitsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar to the results in previous studies (Koslo et al, 1986;Heyman et al, 1988;Pol et al, 1999;Ross et al, 2008), we showed that morphine can inhibit gastrointestinal transit mainly through peripheral, and in part through supraspinal as well as spinal, naloxonazine-insensitive sites of m-opioid receptors, whereas morphine inhibits colonic transit through peripheral naloxonazine-sensitive and -insensitive sites of m-opioid receptors. In the present study, we showed that oxycodone and fentanyl inhibit gastrointestinal transit mainly through peripheral m-opioid receptors.…”
Section: Differential Effects Of M-agonists On Intestinal Transitsupporting
confidence: 80%
“…Previous studies have demonstrated that intracentroventricular and intrathecal administration of morphine inhibits gastrointestinal and colonic function (Koslo et al, 1986;Heyman et al, 1988;Pol et al, 1999), whereas peripheral m-opioid receptors also contribute to morphine-induced intestinal movement in rodents (Gmerek et al, 1986;Pol et al, 1999;Ross et al, 2008). On the other hand, naloxonazine could not reverse the morphine-induced inhibition of gastrointestinal transit, even though it reversed the morphine-induced (intrathecally) inhibition of gastrointestinal transit (Heyman et al, 1988), and partially reversed the morphine-induced inhibition of colonic transit (Koslo et al, 1986).…”
Section: Differential Effects Of M-agonists On Intestinal Transitmentioning
confidence: 99%
See 1 more Smart Citation
“…Placebo or chronic morphine administration was achieved by the subcutaneous implantation of a placebo or 75-mg morphine pellet (National Institute on Drug Abuse, Rockville, MD) under aseptic conditions and 2.5% isoflurane anesthesia as previously described elsewhere (Ross et al, 2008). Using morphine pellets is a standard method for continuously administering morphine to prevent cycles of withdrawal in mice, and it produces brain drug levels considered to be similar to blood/tissue levels achieved in humans who are tolerant and dependent on opiates (Ozaita et al, 1998;Ghazi-Khansari et al, 2006), and therapeutic levels seen in patients maintained on chronic opiates/ opiate pumps for intractable pain (Balch and Trescot, 2010).…”
Section: Placebo or Chronic Morphine Administrationmentioning
confidence: 99%
“…Pellets were implanted as previously described (Ross et al, 2008). Mice were anesthetized with 2.5% isoflurane, and the hair on the back of their neck was shaved.…”
Section: Methodsmentioning
confidence: 99%